(untitled) (KYAMC Journal, 2024)
Background: Oral cancer is a frequent cancer in our country, most people are affected by this cancer are older age. Accurate evaluation of this cancer difficult due to close proximity of bones and soft tissue. So for improve diagnostic accuracy Puffed cheek maneuver should be used with traditional Multidetector Computed Tomography (MDCT). Objective: To determine the improved diagnostic accuracy of Puffed cheek Computed Tomography (PCCT) in evaluation of buccal mucosa tumors in contest to non puffed cheek Computed Tomography. Materials and Methods: This descriptive cross sectional study was carried out in Radiology and Imaging department of Khwaja Yunus Ali Medical College and Hospital from 2022(January) to 2023(July). Cases were referred from different department. After meeting the inclusion criteria patients were subjected for CT scan. Imaging was performed from paranasal sinus and neck region with axial sections from pituitary fossa to arch of aorta, after injection of intravenous iodinated contrast media, multiplanar sagittal, coronal reformation images were obtained. Puffed cheek manoeuvre was performed to separate gingival and oral buccal mucosa in all the cases for improved detailed evaluation. The CT result were then compared with non puffed cheek scans results. Results: Among 30 patients 7 cases were missed by conventional CT scan, thirteen patients showed a mass in the oral cavity that were inseparable from 2 mucosal surfaces. Puffed-cheek images clearly showed the mass and surface of tumor involvement. Other 10 patients in conventional CT showed mass in the margins of tongue, oral cavity but extension and infiltration of surrounding structures by the lesion could not be well delineated, puffed-cheek images clearly showed the specific location, extension, adjacent muscles and other structures infiltration. Conclusion: Puffed cheek CT gives better performance to diagnosis the small buccal mucosal tumors, any irregularity, thickening, more detailing of mucosal surface of oral cavity than conventional CT scan, so can helps in choosing the management & surgical approach also. KYAMC Journal Volume: 15, No: 01, April 2024: 29-32.